Penerapan Manajemen Risiko Berbasis ISO 31000 dengan Analisis SWOT dan Matriks Risiko pada UMKM Caca Cell - Siti Azmi Nur Islami; Ashilah Fauziyah; Yesica Maulina; Umu Mahmudah; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze risk management in the Caca Cell micro-enterprise by using the ISO 31000 framework combined with the SWOT and Risk Matrix analysis. Caca Cell is a micro-enterprise focused on providing credit and internet services so that in the implementation of activities there are operational and non-operational risks this study uses qualitative descriptive methods through observation and interviews to identify and evaluate risks that can affect sustainability an effort. Research results show that there are 11 risk events, consisting of 3 high-category risks, 6 medium-category risks, and 2 low-category risks. High-category risks are primarily derived from marketing, operational and financial aspects. Risk Treatment At the last stage, risk treatment is performed for each risk-bearing event in Caca Cell which is already grouped by their respective risk levels. Implementation of the ISO 31000 framework can assist Caca Cell in identifying, assessing, and managing risks more systematically and sustainably. This effort is expected to increase the effectiveness of risk control and support the sustainability of business operations in the midst of competition in pulse counter businesses